International Conference on Informatics Research for Development of Knowledge Society Infrastructure, 2004. ICKS 2004.
DOI: 10.1109/icks.2004.1313425
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to numerical algorithms in terms of integrable systems

Abstract: Almost four decades passed after the discovery of solitons and infinite dimensional integrable systems. The theory of integrable systems has had great impact to wide area in physics and mathematics. In this paper an approach to numerical algorithms in terms of integrable systems is surveyed. Some integrable systems of Lax form describe continuous flows of efficient numerical algorithms, for example, the QR algorithm and the Jacobi algorithm. Discretizations of integrable systems in tau-function level enable us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The right-hand-side of ( 19) defines orispherical coordinate system (q n , z nm ), n > m, on the space of symmetric positive-definite matrices G. Explicit time dependence of G(t) given by (19) provides that…”
Section: [H A]]mentioning
confidence: 99%
See 1 more Smart Citation
“…The right-hand-side of ( 19) defines orispherical coordinate system (q n , z nm ), n > m, on the space of symmetric positive-definite matrices G. Explicit time dependence of G(t) given by (19) provides that…”
Section: [H A]]mentioning
confidence: 99%
“…The connection between the recursion method and Toda chain is likely to lead to new practical improvements in numerical applications, as suggested by many other uses of Toda chain in the context of computational algorithms [19].…”
Section: [H A]]mentioning
confidence: 99%
“…For such a connection, see also [203,219]. Other equations are related to acceleration methods [205]. For example in [204], the authors wrote abstract.…”
Section: Integrable Systemsmentioning
confidence: 99%
“…With appropriate discretization, for example, it can be shown that the above formula leads to the Rutishauser qd algorithm (Nakamura 2004, Rutishauser 1954. Instead of detailing here how this can be done for the eigenvalue computation which is a well studied subject, we shall demonstrate a similar application to the much more sophisticated singular value decomposition in the next section.…”
Section: Tau Functions and Determinantal Solutionmentioning
confidence: 99%